Gender, Voice and Silence: Strategies for Inclusion of Female Employees - Fapohunda, Tinuke. M. (Archives of Business Research, 2016)
Employee voice has been mostly scrutinized as a general idea with inadequate attention to workforce gender diversity. Diverse employees present an important central position from which to study employee voice instruments. Female employees are often silenced by what is recognized as usual in work organizations. The lack of physical markers for gender differentiation, the deficiency of legal protections in many locations, the comparative need of union support, and the prevalent downbeat attitudes toward the female gender consequence in more silence for women employees than for men. This paper identifies some of the antecedents and harmful corollaries of such silencing and suggests ways in which the voices of female employees can be heard, arguing that effective management of gender diversity and inclusion would embrace machineries of voice through which gender differences are identified and organizational appraisals conducted to contain those differences in the procedures of decision making and career development. The status quo can shift by breaking the cycle of invisibility and silence by giving female employees room to make constructive contributions to work, unobstructed by fear of violence, prejudice, discrimination, and harassment. To achieve this plan, organizations must develop voice mechanisms that include the specific needs of women employees’ in the workforce. Specific recommendations are provided for HR managers to facilitate the expression of voice for female employees in today’s increasingly diverse organizations.